The relationship between skill based volunteerism and job performance among volunteers in Malaysia. - Veerasamy, Chanthiran; Kumar, Naresh (2012)
The importance of volunteerism and job performance to the competitive strength of modern organization has become common astuteness. The challenge is to encourage skill based volunteerism via unremitting research to ensure optimum development of volunteers at various levels within an organization. The identification of mechanisms to facilitate skill based volunteerism is noteworthy on the road to enhance job performance. A mailed survey was carried out with a sample of 366 skill based volunteers with some significant findings. The important finding of the study is the significant positive relationship between skill based volunteerism (frequency and duration) and job performance (focal and contextual). The study provides strong support and a better understanding on the contribution of skill based volunteerism towards high, sustained job performance of volunteers at their workplace. The findings generally resonate with the positions taken by social work researchers. Besides, the exploratory study provides a data-base to develop new strategies, further research and review of the social policy pertaining to volunteerism.